Implementasi Program Tahfiz Qur’an dalam Menciptakan Budaya Sekolah Berbasis Qur’ani di SMP Negeri Kabupaten Aceh Utara: Penelitian - Agustina; Iis Marsithah; Nurlaili; Erniningsih; Vonna Rohaza; Mariana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the implementation of the Tahfiz Qur'an program in creating a Qur'ani-based school culture at public junior high schools in North Aceh Regency. The Tahfiz Qur'an program is a strategic effort to foster religious character, noble morals, and Islamic insight among students amid the current moral challenges faced by young generations. This research employs a descriptive qualitative approach using observation, interviews, and documentation techniques. The results indicate that the program is implemented through curriculum integration, daily and weekly scheduling, guidance by religious teachers and hafiz, as well as regular evaluations. Its impact is reflected in the formation of an Islamic school culture, shown by habits of reading the Qur'an, increased discipline, and Islamic values in social interactions. The challenges encountered include a shortage of qualified Tahfiz instructors, students’ varying memorization abilities, and time management issues. Solutions applied include teacher training, personal motivation approaches, and collaboration with Islamic boarding schools and parents. This program has proven effective in establishing a Qur'ani culture that is not merely symbolic but practically embedded in everyday school life.